The quranic da'wah of Bediuzzaman Said Nursi: a review / Faridah Mohd Sairi ... [et al.] - Mohd Sairi, Faridah; Md Soh, Noor Syahida; Ayob, Mohd Annas Shafiq; Mohamad Zaini, Mohd Norazri (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2023)
Bediuzzaman Said Nursi, a renowned Islamic philosopher, started composing his Rasail al-Nur collection when he was being held in Barla. His pamphlets became an effective tool for spreading the miracles of Al-Quran and the pillars of faith (Rukun Iman). This study examines the fundamental Quranic teachings used by Bediüzzaman Said Nursi to disseminate his da'wah. This research utilizes a descriptive qualitative study. The qualitative data was obtained via interviews, documents, and analysis. The study reveals six fundamental doctrines of Bediüzzaman Said Nursi’s da'wah method, derived from his books, Rasail al-Nur. The six principles served as the foundation for the Quranic methodology that includes first, to serve faith (iman) and the Quran; second, sincerity; third, brotherhood and kinship; fourth, al-'ajzu (weakness), syafaqah (sympathy), poverty, and reflection; fifth, firmness and loyalty; and sixth, resolving and unwavering gratitude. The six Quranic principles underlying Bediüzzaman Said Nursi's da'wah are the fundamental building blocks for comprehending the effectiveness of his da'wah, which has successfully spread throughout the world, particularly in Turkey.